Proteome and Structural Organization of the Knob Complex on the Surface of the Plasmodium Infected Red Blood Cell. Issue 4 (5th December 2017) - Alampalli, Shuba Varshini; Grover, Manish; Chandran, Syama; Tatu, Utpal; Acharya, Pragyan
Abstract : Purpose: The cell membrane of the erythrocytes infected with the malaria parasite Plasmodium falciparum undergoes several changes during the course of parasite life cycle and forms protrusions known as 'knobs' on its surface during the mature trophozoite and schizont stages. The structural organization of knob components especially PfEMP1 on the iRBC surface is the main determinant for the cytoadhesive and rosetting capacity of the iRBC by binding to various host receptors as well as for the variable antigenicity, which is crucial for immunoevasion. Although several studies report individual interactions among knob constituents, a comprehensive identification of the knob proteome is lacking. Experimental design: The detergent‐resistant membrane (DRM) rafts are isolated from the infected erythrocyte membrane and knob (KAHRP) positive fractions are subjected to proteomics analysis. In addition, structures of various knob components are modeled and assembled ab initio based on experimentally established protein interactions. Results: Proteins of various functional classes are found to be present in the knobs including the newly identified knob constituents which include host Hsp70, elongation factor 1A, acyl CoA synthetase, and some hypothetical proteins. Ab initio structural prediction of PfEMP1, KHARP, PfEMP2, PfEMP3, and PHIST shows that these proteins are intrinsically disordered and can have varying number of protein–protein interactions depending on their lowest energy structure. Further in silico mathematical modeling of a single repeat unit of PfEMP1–PHIST is present 63–112 times along the periphery of a single knob. Conclusions and clinical relevance: This study provides structural insight into the organization of the core knob components and uncovers novel proteins as knob components. This structural information can be used for the development of better vaccine design strategies or drug design to destabilize the knob structure, which is a major virulence determinant in P. falciparum malaria.